Early implementation of guidelines for managing young infants with possible serious bacterial infection in Bangladesh. Issue 6 (19th November 2019) - Applegate, Jennifer A; Ahmed, Sabbir; Khan, Marufa Aziz; Alam, Sanjida; Kabir, Nazmul; Islam, Munia; Bhuiyan, Mamun; Islam, Jahurul; Rashid, Iftekhar; Wall, Steve; de Graft-Johnson, Joseph; Baqui, Abdullah H; et al.
Abstract : Neonatal infections remain a leading cause of newborn deaths globally. In 2015, WHO issued guidelines for managing possible serious bacterial infection (PSBI) in young infants (0–59 days) with simpler antibiotic regimens if hospital referral is not feasible. Bangladesh was one of the first countries to adapt WHO guidance into national guidelines for implementation in primary healthcare facilities. Early implementation was led by the Ministry of Health and Family Welfare (MOHFW) in 10 subdistricts of Bangladesh with support from USAID's MaMoni Health System Strengthening project. This mixed methods implementation research case study explores programme feasibility and acceptability through analysis of service delivery data from 4590 sick young infants over a 15-month period, qualitative interviews with providers and MOHFW managers and documentation by project staff. Multistakeholder collaboration was key to ensuring facility readiness and feasibility of programme delivery. For the 514 (11%) infants classified as PSBI, provider adherence to prereferral treatment and follow-up varied across infection subcategories. Many clinical severe infection cases for whom referral was not feasible received the recommended two doses of injectable gentamicin and follow-up, suggesting delivery of simplified antibiotic treatment is feasible. However, prereferral antibiotic treatment was low for infants whose families accepted hospital referral, which highlights the need for additional focus on managing these cases in training and supervision. Systems for tracking sick infants that accept hospital referral are needed, and follow-up of all PSBI cases requires strengthening to ensure sick infants receive the recommended treatment, to monitor outcomes and assess the effectiveness of the programme. Only 11.2% (95% CI 10.3 to 12.1) of the expected PSBI cases sought care from the selected service delivery points in the programme period. However, increasing trends in utilisation suggest improved awareness and acceptability of services among families of young infants as the programme matured. Future programme activities should include interviews with caregivers to explore the complexities around referral feasibility and acceptability of simplified antibiotic treatment.